Caminhos do Interior: Connecting Information Systems, Tourism, and Regional Development in Brazil's Inland - Araújo, Allysson Allex; Sousa, Joel; Duarte, Vicente; Bessa, Thiago; Kalinowski, Marcos (Anais Estendidos do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2024: Anais Estendidos do XX Simpósio Brasileiro de Sistemas de InformaçãoDO - 10.5753/sbsi_estendido.2024.238676, 2024)
This paper introduces the ''Caminhos do Interior'', a proposal of web-based solution aimed at promoting regional development through tourism in the lesser-explored areas of Brazil. Drawing from an interdisciplinary and sociotechnical perspective, this project merges concepts of under tourism and city branding to curate and spotlight tourist attractions. We provide a web-based high-fidelity prototype showcasing regional attractions, city profiles, and a categorization of tourist activities. With potential impacts spanning academia, industry, and policy, our initiative contributes to the literature and practice by investigating the role of Information Systems (IS) in promoting regional growth and enriching the understanding of the interplay between IS, tourism, and socioeconomic development. Furthermore, we intend to offer practical and socially aware insights by demonstrating the role of an IS in attracting tourists, investors, entrepreneurs, and strengthening regional economies.